Acceptability and feasibility of self‐sampling and follow‐up attendance after text message delivery of human papillomavirus results: A cross‐sectional study nested in a cohort in rural Tanzania. (12th March 2021) - Mremi, Alex; Linde, Ditte S.; Mchome, Bariki; Mlay, Joseph; Schledermann, Doris; Blaakær, Jan; Rasch, Vibeke
Abstract: Introduction: The objective was to determine if self‐collection of vaginal samples for human papillomavirus (HPV) testing was acceptable and feasible in rural Tanzania and to assess the extent of attendance at a follow‐up appointment among women who tested HPV‐positive after delivery of HPV results via text messages. Material and methods: A combined cross‐sectional and cohort study was conducted among women aged 25‐60 years from rural Kilimanjaro, Tanzania. Women were offered HPV self‐sampling or traditional visual inspection of the cervix with acetic acid. If HPV self‐sampling was preferred, participants received instructions on self‐collection with an Evalyn Brush. A questionnaire was used to assess the acceptability and feasibility of the self‐sampling procedure for the participants and delivery of HPV results via text messages. A mobile text message platform was used to send private text messages with the screening results to the participants. Results: A total of 1108 women were enrolled and self‐collected an HPV sample; 11.8% tested positive for high‐risk HPV. The majority (98.9%) agreed that they had no trouble in understanding the instructions on how to perform the self‐collection and that they would recommend it to a friend (94.5%) or as a standard screening method in Tanzania (95.5%). A minority of women experienced bleeding (2.4%) or pain (6%) while collecting the sample, while some were worried that they would get hurt (12.7%) or felt embarrassed (3.5%). The majority (98.4%) of women would like to receive the screening test results via text messages. Eighty‐two per cent of those who tested positive for high‐risk HPV attended the follow‐up appointment after receiving a text message reminder and an additional 16% attended after receiving both a text message and a phone call reminder whereas 2% did not attend follow up at all. Attendance was not influenced by age, marital status, education level, parity, or HIV status. Conclusions: Human papillomavirus self‐sampling and text‐message feedback delivery are generally well‐perceived and accepted among rural Tanzanian women, and the majority of HPV‐positive women attended a follow‐up appointment after receiving their HPV results and follow‐up appointment via text messages. This screening method may have potential to be transferrable to other low‐income countries with a high incidence of cervical cancer and so improve cervical cancer screening attendances.